Optimal land and water management - A case study of Krishi Vigyan Kendra Bilaspur, Chhattisgarh - CHANDNIHA, SURENDRA KUMAR; SINHA, JITENDRA; KHALKO, DHIRAJ; TRIPATHI, M.P.; WADWARE, PRATIBHA (Journal of Soil and Water Conservation, 2022)
In present study area, it was noticed that rainwater comes during early monsoon and found dry spells at critical crop growing periods. For the management point of view, it has to be suggested that rainwater has to be collected in early monsoon period and to be utilized in deficit period using the storage structures. Water storage structure has to be attained the solution to this problem in deficit condition of rainfall in kharif as well as rabi seasons. For the purpose, this study has been conducted in Krishi Vigyan Kendra (KVK) farm, Bilaspur. Conservation Factor (CF) has been adopted for runoff estimation over the study area. Initially topographic survey has been made using the dumpy level at every 10m × 10m grids. Further existing inventory and landuse pattern have also identified using the topographic survey and ground-truthing. Thereafter, mapped and characterized according to landuse capability classification. In present study, runoff has been estimated using Soil Conservation Society Curve Number (SCS-CN) and CF methods as per existing rainfall. Probable rainfall and runoff have been estimated at four different probability of exceedance i.e., 50, 60, 70 and 80 percent. Based on estimated runoff at different level of exceedance, design of farm pond has been suggested. Shape of farm pond are also designed in rectangular, square and circular forms. Optimal crop planning has been suggested using the simplex method of optimization as per capacities of farm pond at different levels of exceedance. Optimal model has been developed with objective function and constraints. Further, linear programming technique is adopted for solving the objective functions using TORA (ver. 1.0) software. Thereafter, optimal solution has been suggested for maximum benefit-cost ratio. At last water collection ponds designed have been suggested at 50, 60, 75 and 80 percent probabilities of exceedence.